The assessment of sarcopenia and the frailty phenotype in the outpatient care of older people: implementation and typical values obtained from the Newcastle SarcScreen project - R. M. Dodds; P. Heslop; Jafar; Davies; Noble; Shaw; Witham; Sayer (My University, 2022)
Purpose Sarcopenia and the frailty phenotype both indicate older adults at risk of adverse health outcomes and yet are not widely assessed in practice. We developed the Newcastle SarcScreen to enable assessment of these two ageing syndromes during clinical care. In the setting of our Older People’s Medicine Day Unit, our aims were to describe the implementation of the SarcScreen and to examine the typical values obtained. Methods The SarcScreen comprised height, weight, questions (three on the Fried frailty phenotype and fve on the SARC-F questionnaire), grip strength and gait speed. We analysed data from 552 patients completing the SarcScreen. We expressed grip strength as Z-scores (number of standard deviations above the mean expected for a patient’s age and sex). Results It was possible to implement the SarcScreen. In 552 patients (65.9% females) with mean age 80.1 (7.7) years, grip strength was feasible in 98.2% and gait speed in 82.1%. Gait speed was typically not assessed due to mobility impairment. Most patients had weak grip strength (present in 83.8%), slow gait speed (88.8%) and the frailty phenotype (66.2%). We found a high prevalence of probable sarcopenia and the frailty phenotype across all age groups studied. This was refected by low grip strength Z-scores, especially at younger ages: those aged 60–69 had grip strength 2.7 standard deviations (95% CI 2.5–2.9) below that expected. Conclusion It is possible to implement an assessment of sarcopenia and the frailty phenotype as part of the routine outpatient care of older people.
Keywords: Sarcopenia · Frailty · Grip strength · Walking speed · Implementation · Usual care